Property heterogeneity and convergence club formation among local house prices (2019)
We investigate the extent of convergence club formation in local house prices. Our study is novel in a number of key ways. First, new insights are obtained through utilising a large disaggregated panel dataset comprising multiple types of housing (detached, semi-detached, terraced housing and flats) for a very large sample of 348 England and Wales local authorities. Second, we analyse through probit estimation those factors that drive convergence club formation. Third, we also consider within-city club formation as well as club formation during periods of house price bubbles. Using a study period of more than two decades, we find the presence of divergence or multiple house price convergence clubs rather than a single club. While location, distance, income, population density, congestion and education are significant in explaining convergence club formation, housing type is also an important factor with convergence less likely among detached, semi-detached and terraced housing than among flats. © 2018 Elsevier Inc.